2013
DOI: 10.3329/bmrcb.v38i3.14328
|View full text |Cite
|
Sign up to set email alerts
|

Surgery for primary intracerebral haemorrhage: is it safe and effective?

Abstract: This prospective study was conducted to compare the outcome between medical and surgical treatment of primary intracerebral haemorrhage at the department of Neurosurgery, Dhaka Medical College

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…Talukder et al, [27] as they showed no difference in outcome (p-value 0.667) of ventricular extension between surgical and conservative group, In other hand…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations
“…Talukder et al, [27] as they showed no difference in outcome (p-value 0.667) of ventricular extension between surgical and conservative group, In other hand…”
Section: Discussionmentioning
confidence: 88%
“…The most common presentation of our patients was deterioration of the conscious level which reported in 12 cases out of 20 patients (60%), Pantazis et al, [30] found 42% of their cases presented with deteriorated consciousness. Cuatico et al, [31] and Talukder et al, [27] stated that the significance of level of consciousness the most important single clinical signs determining the prognosis, the same result we had in our study as we had 5 patients with GCS ≤ 8 (25%) all of them (100%) died regardless the type of treatment, which indicated that when the initial GCS is less than "8" mortality is high, similar results were found by different studies [32] [33] [34] The risk for early neurological deterioration and the high rate of poor long-term outcomes underscores the need for aggressive early management Steiner et al, [35].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite the frequency of ICHs, there is still ongoing debate about the optimal patient care. The treatment strategies include medical, surgical and combined treatment, including emergent reduction of blood pressure and coagulopathy reversal, management of cerebral oedema, as well as surgical interventions [4,10,[12][13][14]. The latter include External Ventricular Drainage (EVD) and hematoma evacuation [1,6].…”
Section: Discussionmentioning
confidence: 99%